2011
DOI: 10.4103/1319-3767.74470
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive predictors of esophageal varices

Abstract: Background/Aim:Current guidelines recommend screening cirrhotic patients with an endoscopy to detect esophageal varices and to institute prophylactic measures in patients with large esophageal varices. In this study, we aimed at identifying non-endoscopic parameters that could predict the presence and grades of esophageal varices.Patients and Methods:In a prospective study, 229 newly diagnosed patients with liver cirrhosis, without a history of variceal bleeding, were included. Demographic, clinical, biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 19 publications
2
17
1
1
Order By: Relevance
“…Up to now, endoscopy has still been the gold standard modality to identifying esophageal varices [ 1 ]. However many studies attempt to identify noninvasive factors predicting the presence and the grade of esophageal varices [ 2 , 3 ]. Several Studies have shown that multiple parameters can be a predictors for the presence of oesophageal varices like splenomegaly, [ 4 6 ] ascites [ 4 ], spider naevi [ 7 ], Child's grade [ 6 , 7 ], platelet count [ 7 10 ], prothrombin time/activity [ 8 ], portal vein diameter [ 11 ], platelet count/ spleen diameter ratio [ 11 , 12 ], serum albumin [ 12 ], and serum bilirubin [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, endoscopy has still been the gold standard modality to identifying esophageal varices [ 1 ]. However many studies attempt to identify noninvasive factors predicting the presence and the grade of esophageal varices [ 2 , 3 ]. Several Studies have shown that multiple parameters can be a predictors for the presence of oesophageal varices like splenomegaly, [ 4 6 ] ascites [ 4 ], spider naevi [ 7 ], Child's grade [ 6 , 7 ], platelet count [ 7 10 ], prothrombin time/activity [ 8 ], portal vein diameter [ 11 ], platelet count/ spleen diameter ratio [ 11 , 12 ], serum albumin [ 12 ], and serum bilirubin [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…This factor was also significant on multivariate analysis. Several studies suggest that platelet count may predict the presence of EV in patients with cirrhosis [ 2 , 8 , 9 ]. However, the discriminating threshold for the presence of varices varies widely, ranging between 68,000 and 160,000/mm 3 [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Univariate logistic regression followed by a multivariate logistic regression model was employed to calculate the odds ratio (OR) at 95% confidence interval (CI) to assess the degree of association between different factors and the presence of esophageal varices. On the basis of previous literatures [12, 13, 1720], and our own clinical experience we selected age, sex, alcohol use, jaundice, ascites, hepatitis status, platelet counts (PTC), hemoglobin level, serum albumin, portal vein diameter (PVD), splenic diameter (SPD), and Child-Pugh score as potential predictors of esophageal varices. Parameters including hepatic encephalopathy, serum bilirubin, serum albumin, ascites and international normalized ratio (INR) were used to calculate the Child-Pugh score as done previously [21].…”
Section: Methodsmentioning
confidence: 99%
“… 64 67 Other blood tests that were determined to predict varices were platelet count (sensitivity 56-76%; specificity 64-88%) and AST-to-platelet Index (sensitivity 59-86%; specificity 64-81%). 62 64 68 69 70 Among the doppler ultrasound parameters only hepatic artery resistive index was found to be associated with presence of varices. 55 57 …”
Section: Varicesmentioning
confidence: 95%